1995
DOI: 10.1073/pnas.92.21.9570
|View full text |Cite
|
Sign up to set email alerts
|

A histologically distinctive interstitial pneumonia induced by overexpression of the interleukin 6, transforming growth factor beta 1, or platelet-derived growth factor B gene.

Abstract: A histologically distinctive interstitial pneumonia induced by overexpression of the interleukin 6, transforming growth factor 131, or platelet-derived growth factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 25 publications
3
80
1
3
Order By: Relevance
“…Moreover, intrapulmonary transduction of both IL-6 and IL-6 receptor genes resulted in lymphocytic infiltration with negligible fibrotic changes [21]. It can therefore not be excluded that one or more additional factors may mediate the fibrosis-inducing activities of IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, intrapulmonary transduction of both IL-6 and IL-6 receptor genes resulted in lymphocytic infiltration with negligible fibrotic changes [21]. It can therefore not be excluded that one or more additional factors may mediate the fibrosis-inducing activities of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, major collagen-producing cells in liver, which are fat-storing cells, were seen in vitro to be able to produce IL-6 [15] and express collagen mRNA in response to IL-6 [16], and continuous administration of IL-6 could induce liver fibrosis [17]. However, IL-6 transgenic mice exhibited no apparent fibrotic changes in any organs [18][19][20], whereas intrapulmonary transduction of the IL-6 gene induced lymphocytic alveolitis without fibroblast proliferation, whereas that of the TGF-␤ 1 or the PDGF B gene induced significant fibroblast proliferation and deposition of collagen [21]. Thus, the functions of IL-6 in fibrotic changes remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…35 Yoshida and co-workers demonstrated that overexpression of the genes encoding both PDGF-B chain and TGF-␤1 in rats resulted in interstitial lung fibrosis. 36 Furthermore, it is noteworthy that PDGF-AA is essential to the development of myofibroblasts in the embryonic lung. 37 Collectively, these studies provide strong evidence that the PDGF system is pivotal to mesenchymal cell growth in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of PDGF-B in mice, under control of the surfactant C promoter, led to pulmonary fibrosis accompanied by emphysema-like changes (14). Consistently, adenovirally induced overexpression of PDGF-BB also resulted in mild pulmonary fibrosis (15). Overexpression of PDGF-A or PDGF-B chains in organs other than the lungs resulted in tissue fibrosis as well (16).…”
Section: Pdgf and Pdgfr In Sscmentioning
confidence: 65%